The impact of artificial intelligence applied in businesses on economic growth, welfare, and social disparities - Adela Socol; Andreea Marin-Pantelescu; Tamas-Szora Attila; Ionela Cornelia Cioca (Amfiteatru Economic Journal, 2024)
Previous literature on the impact of the application of artificial intelligence in businesses on economic growth, welfare, and social disparities is scarce, due to limited data and the recent dynamics of the field. To contribute to this gap, the study employs the percentage of large enterprises in the European Union (EU-27) using artificial intelligence technologies in production for the year 2021. The results obtained by static analysis (Feasible Generalized Least Squares method) indicate positive relationships between the application of artificial intelligence in large enterprises in European Union countries and economic growth, while the analysis of welfare and social disparities leads to mixed results: increasing the average net income per person, respectively, the poverty threshold and decreasing the number of people at risk of poverty and unemployment. Spatial analysis (Spatial Lag Model) of the economic and social impact of artificial intelligence applied in a country's large enterprises on neighbouring countries leads to robust results for economic growth and net average income per person, whose levels are positively influenced, through spillover effects and spatial interactions between states. At the microeconomic level, the study highlights the need for rapid adaptation of enterprises to artificial intelligence, and from the perspective of public policies, the need for transparent and sustainable regulations.
Keywords: O11; B55; O33; C58; O52; 330; Artificial intelligence (AI); enterprises; European Union; growth; unemployment; welfare